Investigation of Community Engagement in Sustainable Construction Projects: Case Studies from Nigeria - Unegbu, Hyginus C. O.; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Journal of Sustainable Construction, 2024)
This study investigates the role of community engagement in sustainable construction projects in Nigeria, focusing on three case studies: a green residential building in Lagos, an eco-friendly community center in Abuja, and a sustainable water infrastructure project in rural Kano. Using a mixed-methods approach, data were collected through  interviews, surveys, and document analysis. The research identifies significant variations in engagement practices, with Lagos showing high engagement levels, leading to greater community acceptance and better environmental outcomes. Key success factors include strong leadership, adequate funding, and effective communication, while challenges such as socio-cultural barriers and political interference were noted. The findings emphasize the importance of sustained, tailored engagement strategies to enhance project sustainability and community support. This study contributes to the literature by providing empirical data on the long-term impacts of community engagement, offering insights for policy makers and project managers to improve community participation in sustainable construction.